RUANG LINGKUP KOMUNIKASI HUKUM PIDANA DAN PERDATA SEBAGAI BUKTI KEJAHATAN: KAJIAN PUSTAKA ATAS KEABSAHAN, KEKUATAN PEMBUKTIAN, DAN PERLINDUNGAN HAK DALAM PENGGUNAAN KOMUNIKASI LISAN, TERTULIS, ELEKTRONIK, DAN DIGITAL SEBAGAI ALAT BUKTI - Gunawan Widjaja (ADISAM PUBLISHER, 2026)
This article examines the scope of criminal and civil law communications as evidence of crime through a literature review approach, focusing on the validity, probative value, and protection of rights in the use of oral, written, electronic, and digital communications as evidence. In criminal law, communication serves as a means of evidence that must meet formal and material requirements, including a minimum of two valid means of evidence, while in civil law, communication is emphasised more on relevance and preponderance of evidence. Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law) recognises electronic information and documents as an extension of valid evidence, provided that they can be accessed, displayed, guaranteed to be complete, and accountable. The validity and probative value of communication are determined by factors of authentication, data integrity, and the means of acquisition. Electronic evidence that has not undergone an adequate digital forensics process is often only considered as supplementary or preliminary evidence, so it needs to be reinforced with other evidence to meet higher standards of proof, especially in criminal cases. In practice, courts reject some electronic evidence because it was obtained through unlawful means, such as wiretapping without court authorisation or the collection of personal data without consent, making the protection of rights a determining factor in the admissibility of communication evidence. The use of communications as evidence of crime must also be balanced with the protection of human rights, particularly the rights to privacy, freedom of communication, and the right to defence. Wiretapping, monitoring, or collection of electronic communication data without valid authorisation has the potential to violate privacy rights and may result in the rejection of evidence by the court. Therefore, digital communication-based evidence needs to be regulated within a clear regulatory framework, including digital forensic technical standards and oversight mechanisms, in order to maintain justice, legal certainty, and public trust in the judicial system.